An Inspired Self-Organizing Emergent Approach for Autonomous (IoT) Systems - Bekkai, Basma; Bendjenna, Hakim; Ilham, Kitouni (Communications in Mathematics and Applications, 2021)
The IoT progressively happens in effective applications like security equipment, military and medicine use, transportation control, smart communications, meteorology methods. As long as these applications dimension is dreadful, appliance abilities are limited, specifically when it comes to delays and power consumption. IoT is a prototype like any human-made establishment which is exposed to interruptions, catastrophes, and different contradictory circumstances. Supplied communications fail in such conditions, interpreting this prototype with almost no utility. Therefore, network self-organization amongst these appliances would be required so as to empower communication flexibility and afterwards operative system. This article aims to suggest a selforganizing emergent approach for the IoT inspired by the nerve cell’s mechanism. For every node across the network, it may interact efficiently with its neighbors and carry out auto-command in accordance with its standing. In presenting the neuromediator system like the intermediate for transmitting and distributing data, the nodes may work together cooperatively. The aptitude to successfully identify service produced unintentionally may as well be ensured in the potential partly operating IoT by providing the delivery method of neuromediators. To further demonstrate the effectiveness of the proposed approach, we also present a case study and a novel algorithm for autonomous monitoring of power consumption in networked IoT devices.